The Actualization of Character Values in Sumbang Duo Baleh by Teacher Training and Education Students - Syofiani; Hasnul Fikri; Romi Isnanda; Yetty Morelent (Universitas Jambi, Indonesia, 2022)
This research aimed to describe the expression form of character values ​​in Sumbang Duo Baleh by FKIP students at Universitas Bung Hatta. It is quantitative research with a survey approach. The data consist of primary and secondary data. The research subjects are 402 female students of FKIP Universitas Bung Hatta in the academic year 2021/2022 who have a family background and have lived in a social environment with Minangkabau culture for the last three years. The data are collected by distributing a questionnaire through Google Forms that contains an application of Sumbang Duo Baleh in daily life. The results of data analysis show that the application of Sumbang Duo Baleh has not been actualized in the form of character in FKIP Universitas Bung Hatta student’s life. From the twelve points of Sumbang Duo Baleh, it is still in the category of often that shows females from Minangkabau have not applied the twelve Sumbang properly.